Minimally Invasive Treatment of Benign Thyroid Nodules - G. T. Gumerova; G. M. Gubaidullina; F. R. Nagaev; R. R. Bakiev; N. S. Suleymanova (Креативная хирургия и онкология)
Background. Nodular goitre is the commonest pathology of thyroid gland. According to published evidence, the endemic prevalence of iodine deficiency varies within 19–76 % population. The high rates and lack of symptoms at progressive nodules growth warrant the development of effective organ-preserving treatments. Imaging techniques for local precision targeting of individual lesions enable maximum-preserving interventions at thyroid tissue. Today’s world experience of percutaneous ethanol sclerotherapy and radiofrequency ablation is adequate. However, there exist no clear indications for sclerotherapy and radiofrequency ablation, and their consecutive use has not been assessed.Materials and methods. We analyse minimally invasive organ-preserving treatments of benign thyroid nodules (ethanol sclerotherapy, RFA) in 63 patients at the outpatient and general surgery units of BSMU Clinic and MEGI Medical Centre, Ufa, during February 2019 — December 2020.Results and discussion. Ethanol sclerotherapy was highly effective in 46.5 % patients, as evident from discontinued nodule’s blood supply in CDI and B-mode ultrasound, which remained stable in 10.5 % and restored after 3–4 weeks in 25 % patients. Sclerotherapy in colloid goitre was efficient only in 37.5 % patients. Ethanol sclerotherapy was RFA-followed in 25.4 % patients. RFA was favoured at a low-effective sclerotherapy providing for a weak positive dynamics of nodule size, local parietal blood flow preservation and intranodular vessels recanalisation at re-examination.Conclusion. Sclerotherapy was high-effective in cystic nodules. Radiofrequency ablation can be considered most adequate for treating solid nodules. RFA-followed sclerotherapy is a rational choice in treatment of large cystic nodules (>5 cm3 ).